Continued Immunization By Mothers in Children Aged 18 Months Through the Role of Health Workers in Puskesmas Curug Kota Serang - Firdaus, Syahrul; Purnawa, Rachmadi; Widiyaningsih, Cicilia (Journal of Ageing And Family, 2023)
Background: Immunization is one of the most effective health interventions in the world and can save millions of lives. However, in the world there are still more than 19 million children who have not been vaccinated or whose vaccinations are incomplete so that it can cause these children to be very susceptible to disease risk, even though immunization will increase the child's immune system. The purpose of the study was to analyze and explain the influence of predisposing factors (knowledge, education, mother's occupation, husband's support and participation of health workers) on the provision of follow-up immunization to children aged 18 months at the Curug Health Center in Serang City in 2021. Methods: Using a quantitative approach with a cross sectional design. A sample of 101 respondents. Data analysis was carried out using univariate analysis, which describes the frequency distribution, bivariate analysis to determine the relationship between variables and multivariate analysis with linear regression analysis. The results of this study found that there was a relationship between knowledge, education, work, husband's support and communication and services of health workers with the provision of further immunization for children aged 18 months at the Curug Health Center in Serang City in 2021. The most dominant variables were the communication and service variables of health workers. It is hoped that the Curug Health Center can provide counseling or education about the importance of providing immunizations to patients, especially mothers who have toddlers on a regular basis. Keywords: Provision of follow-up immunization to children aged 18 months, knowledge, education, work, husband's support and communication and services.